Cue Utilization and Cognitive Load in Novel Task Performance - Brouwers, Sue (Front Psychol, 2016)
This study was designed to examine whether differences in cue utilization were associated with differences in performance during a novel, simulated rail control task, and whether these differences reflected a reduction in cognitive load. Two experiments were conducted, the first of which involved the completion of a 20-min rail control simulation that required participants to re-route trains that periodically required a diversion. Participants with a greater level of cue utilization recorded a consistently greater response latency, consistent with a strategy that maintained accuracy, but reduced the demands on cognitive resources. In the second experiment, participants completed the rail task, during which a concurrent, secondary task was introduced. The results revealed an interaction, whereby participants with lesser levels of cue utilization recorded an increase in response latency that exceeded the response latency recorded for participants with greater levels of cue utilization. The relative consistency of response latencies for participants with greater levels of cue utilization, across all blocks, despite the imposition of a secondary task, suggested that those participants with greater levels of cue utilization had adopted a strategy that was effectively minimizing the impact of additional sources of cognitive load on their performance.